Harold Pinter - Baker, William, 1944- (Writers' lives (Continuum (Firm)), 2008)
Harold Pinter is one of the most important writers in English of the late twentieth century and early twenty-first century. This brief biography offers fresh insights into his life and work, concentrating on the themes, patterns, relationships, ideas and language common to his life and creative output. Placing Pinter's life and work alongside each other, the study illuminates Pinter's vision of society, politics, gender, sex, violence and human relationships. Drawing upon the full-range of his output, his letters, journalism, writings about him, Baker combines a biographical approach with clos.